2008
DOI: 10.1016/j.biopsych.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Novel Submicroscopic Chromosomal Abnormalities Detected in Autism Spectrum Disorder

Abstract: Background-One genetic mechanism known to be associated with autism spectrum disorders (ASD) is chromosomal abnormalities. The identification of copy number variants (CNV) i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
238
2
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(250 citation statements)
references
References 19 publications
7
238
2
3
Order By: Relevance
“…For example, UBE3A may act by ubiquitinating SOD1 (Superoxide dismutase 1), which can itself act as a nuclear transcription factor (Mishra et al, 2013;Tsang et al, 2014). SOD1 mutations have been linked to autism (Kovac et al, 2014), which in turn has been linked to maternal 15q11-13 copy number variation that may cause UBE3A overexpression, and to modified phosphorylation that can cause UBE3A hyperfunction (Cook et al, 1997;Christian et al, 2008;Glessner et al, 2009;Hogart et al, 2009;Hogart et al, 2010;Iossifov et al, 2014;Yi et al, 2015). UBE3A also exhibits transcriptional effects independent of its role as an E3 ligase (El Hokayem and Nawaz, 2014).…”
Section: Ube3a In the Nucleusmentioning
confidence: 99%
“…For example, UBE3A may act by ubiquitinating SOD1 (Superoxide dismutase 1), which can itself act as a nuclear transcription factor (Mishra et al, 2013;Tsang et al, 2014). SOD1 mutations have been linked to autism (Kovac et al, 2014), which in turn has been linked to maternal 15q11-13 copy number variation that may cause UBE3A overexpression, and to modified phosphorylation that can cause UBE3A hyperfunction (Cook et al, 1997;Christian et al, 2008;Glessner et al, 2009;Hogart et al, 2009;Hogart et al, 2010;Iossifov et al, 2014;Yi et al, 2015). UBE3A also exhibits transcriptional effects independent of its role as an E3 ligase (El Hokayem and Nawaz, 2014).…”
Section: Ube3a In the Nucleusmentioning
confidence: 99%
“…The absence of additional cases of 2p15-p16.1 deletion in our own ASD study cohort (n¼798), and at least 2586 cases from other published studies [31][32][33][34][35] suggests that the involvement of 2p15-p16.1 with autism is a rare event. Given that the presence of dysmorphic features represents an exclusion criterion for several ASD studies, this may reduce the frequency of detection of 2p15-p16.1 deletions in other screening studies.…”
Section: Discussionmentioning
confidence: 51%
“…To determine the frequency of 2p15-p16.1 deletions among individuals with ASDs, we tested 798 individuals with an ASD for the presence of microdeletions similar to those described in Subjects 1 and 2; none were found. Furthermore, no similar cases have been reported from five other published studies, [31][32][33][34][35] with at least 3410 subjects with an ASD evaluated for CNVs. However, Liang et al 13 reported a case with the 2p15-p16.1 deletion with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Here we shall only point out that the role of CNVs is actually more complex than may appear. Initial studies suggested the existence of genomic instability in a sizable group of ASD patients, because de novo CNVs (i.e., microdeletions or microduplications present only in the patient and not in his/her parents) were significantly more common in autistic compared to healthy individuals [15][16][17]. In reality, the overall number of CNVs was later shown to be similar in ASD cases and controls, while rare CNVs overlapping coding genes are enriched in ASD cases, especially so for loci involved in synaptic and neuronal cell adhesion, ubiquitination, cell proliferation and migration, GTPase/Ras signaling [18][19][20].…”
Section: Trends In Autism Genetic Researchmentioning
confidence: 99%